2014
DOI: 10.1021/ef500854z
|View full text |Cite
|
Sign up to set email alerts
|

Corrosive Properties Prediction from Olive Byproducts Solid Biofuel by Near Infrared Spectroscopy

Abstract: Biofuel characterization constitutes a substantial improvement in the valorization of this resource and allows a rational and controlled use of its energy potential. Corrosion and slagging are primary concerns of solid biofuels; the occurrence and extent of these phenomena depend significantly on the concentration of chlorine in the solid biofuel and the presence of elements such as potassium, sulfur, sodium, phosphorus, calcium, magnesium, iron, or silicon. Solid biofuels quality parameters are being determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The most prominent attributes that affect the NIRS include the C-H stretching overtone related to fat, O-H stretching overtone associated to water, and N-H stretching overtone originating from amides and amines related to the proteins. [31,34] The absorption peaks of spectra shown in Fig. 1a are related to the main components of walnut kernel.…”
Section: Walnut Spectral Profilementioning
confidence: 99%
“…The most prominent attributes that affect the NIRS include the C-H stretching overtone related to fat, O-H stretching overtone associated to water, and N-H stretching overtone originating from amides and amines related to the proteins. [31,34] The absorption peaks of spectra shown in Fig. 1a are related to the main components of walnut kernel.…”
Section: Walnut Spectral Profilementioning
confidence: 99%
“…Studies have also shown the high potential of NIR spectroscopy to predict other solid biofuels parameters such as cellulose, hemicellulose and lignin [22e24], or parameters such as moisture, ash content, calorific value, chlorine and sulfur in olive stone residues [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Pitak et al investigated the possibility of determining C, H, and N via line‐scan near‐infrared (NIR) hyperspectral image technology 100, whereas Mata‐Sanchez et al used NIR to detect Cl, S, and K 101. Furthermore, FTIR coupled with partial least‐squares regression is used to determine the chemical elements like K, Ca, Mg, S, and Si in the study of Edmunds et al 102.…”
Section: Discussionmentioning
confidence: 99%